Analisis Hukum Terhadap Jaminan Sertifikat Tanah yang Bukan Milik Sendiri Berdasarkan Perjanjian Pinjam Pakai dalam KUH Perdata - Faizal Nurkholis (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This research aims to find out and analyze the form of a loan-to-use agreement for a certificate that is not one's own as collateral in the Civil Code and to find out and analyze the role of the collateral recipient in receiving a certificate that is not one's own. This research uses normative legal research, also known as library research, legal research, or legal research instruction, mere secondary data research. Namely examining the law which is conceptualized as legal norms or applicable rules. Data sources were obtained from written sources based on statutory regulations related to the issues discussed. The research results show that borrowing land certificates includes borrowing and not borrowing. However, due to the certificate owner's ignorance, ownership of the land certificate was transferred to the borrower when the owner signed the documents submitted by the certificate borrower. As a result, when the certificate borrower uses the borrowed certificate as collateral, the creditor assumes that the certificate used as collateral belongs to the certificate borrower because the land certificate is in the name of the certificate borrower and the involvement of a third party in guaranteeing land rights can be explained by looking at several articles in the Law. -Law Number 4 of 1996 concerning mortgage rights, namely in article 1 paragraph (2), (3), (4), (6) concerning parties directly involved in mortgage rights, article 4 concerning objects of mortgage rights and article 8 concerning On the subject of mortgage rights, this article appears to provide broad limitations regarding ownership of the land that will be used as collateral.